Reflection technique for the determination of moisture content in hevea rubber latex - Ansarudin, Farizah; Abbas, Zulkifly; Ali, Ali Hamad; Ismail, Mohamad Ali

(untitled)
This paper presents a new technique for the determination of moisture content in hevea rubber latex using an insulated monopole antenna. The antenna was fabricated from a coaxial SMA stub contact panel. The re°ection measurements of hevea rubber latex were carried out using an Agilent Professional Network Analyzer N5230A (PNA) in the frequency range from 0.1 to 4 GHz. The variations in magnitude and phase shift with moisture content were analyzed using regression analysis at several selected frequencies. These in turn were used to establish the relationship in magnitude and phase shift with moisture content. The actual moisture content was determined by the standard oven drying method and compared with predicted values of moisture content. The mean relative errors in the determination of moisture content range from 36.95% to 87.51% using magnitude and phase shift techniques were 0.0505 and 0.0144, respectively.